The relationship between obstructive sleep apnoea and erectile dysfunction: An underdiagnosed link? A prospective cross‐sectional study. (11th July 2022) - Cantone, Elena; Massanova, Matteo; Crocetto, Felice; Barone, Biagio; Esposito, Fabio; Arcaniolo, Davide; Corlianò, Fabrizio; Romano, Luigi; Motta, Gaetano; Celia, Antonio
Abstract: This cross‐sectional study aimed to investigate the prevalence and clinical characteristics of erectile dysfunction in patients with obstructive sleep apnoea. We enrolled 133 male patients with suspected obstructive sleep apnoea. Ear, nose and throat evaluation, laboratory tests, body mass index, Epworth sleepiness scale, 5‐international index of erectile function, overnight ambulatory polygraphy and drug‐induced sleep endoscopy patterns were assessed. Eighty patients reported obstructive sleep apnoea. 60% ( n  = 48) reported erectile dysfunction. Statistically significant correlations were found between 5‐International Index of Erectile Function and age, hypertension, diabetes, Epworth sleepiness scale, apnoea‐hypopnea index score, O2 saturation‐nadir, and oxygen desaturation index. Age, diabetes and O2 saturation‐nadir were independent predictors of erectile function. Epworth sleepiness scale, apnoea‐hypopnea index score, O2 saturation‐nadir, oxygen desaturation index and albumin were higher compared to patients without erectile dysfunction. No statistically significant differences were reported for drug‐induced sleep endoscopy patterns and erectile dysfunction. Patients with obstructive sleep apnoea were at significant risk of having erectile dysfunction. Males with obstructive sleep apnoea should be investigated for erectile dysfunction.